WHY 90% OF STOCK MARKET TRADERS ARE IN LOSS? - Saheelsingh Rajput; Memon Gulammustufa; Jignesh Vidani (Journal of Advanced Research in Accounting and Finance Management, 2024)
This secondary study aims to investigate the widely held belief that a sizable portion, approximately 90%, of stock market traders incur losses. By carefully going over a variety of books, financial statements, and market research, this study seeks to clarify the accuracy of the frequently referenced figure and explore the complex variables that could lead to those results. Our study includes a thorough examination of the psychological, behavioral, and market-related factors that influence traders' profitability. We examine how psychological elements like fear, greed, and overconfidence affect judgment as well as the part played by behavioral biases that could steer traders toward less-than-ideal tactics, all based on empirical data and well-established theories. Simultaneously, the research looks at market dynamics, such as volatility, liquidity, and unanticipated events, in order to identify outside factors affecting trade results. The goal of this research is to provide a comprehensive explanation of the reported high loss rate among stock market traders by combining available knowledge. It also aims to provide insights into possible methods for reducing risk, better decision-making, and raising overall trading success.